A portfolio approach for the selection and the timing of urban planning projects. (June 2021) - Sarnataro, Michele; Barbati, Maria; Greco, Salvatore
Abstract: This paper presents a model to support organizations dealing with urban planning decisions. In particular, we deal with the selection and the timing of several projects that can be realised within an urban development project with the aim of optimizing conflicting objectives. The available resources should be allocated in an acceptable way and current and future requirements must be met. In addition, projects can be characterized by qualitative performances and different scenarios can be considered. The model can be handled with different methods. Given its participatory features, it seems that an interactive multiobjective optimization methodology is the most appropriate approach, since the decision maker can express his opinion throughout the resolution process. We present how the model can work through the description of an application based on the execution of the Master Plan of the University of Portsmouth, one of the most fast progressing University in UK. We show the versatility of the model and how it can successfully handle such complex decisions. Highlights: We define urban planning decisions as a portfolio selection and timing problems. Our problem has a multiobjective formulation that considers a variety of aspects. We are able to handle qualitative information and uncertain conditions. We introduce a structured participatory method to construct the solution. We illustrate our methodology describing the selection of projects in a Master Plan.